MIB-1, AgNOR AND DNA DISTRIBUTION PARAMETERS AND THEIR PROGNOSTIC VALUE IN NEUROENDOCRINE TUMOURS OF THE LUNG - Jütting, Uta; Gais, Peter; Rodenacker, Karsten; Böhm, Joachim; Höfler, Heinz (Image Analysis and Stereology, 2011)
One of the most important questions in clinical routine is to find out patients with good or worse prognosis to apply an optimal therapy scheme for each patient. In this study 58 patients with different neuroendocrine tumours of the lung were investigated. Histological sections were prepared with different stainings (MIB-1, AgNOR, Feulgen). By means of high resolution image cytometry stereological parameters were derived which are indicators for proliferation, ploidy and kinetics of the tumours. Cox regression analysis was calculated to test the significance of the parameters with regard to prognosis. The best parameter was MIB-1 which can easily be applied as a clinical standard staining and measurement.